Tributyltin exposure disturbs hepatic glucose metabolism in male mice. (1st September 2019) - Xu, Jing; Ou, Kunlin; Chen, Chuqiao; Li, Binshui; Guo, Jiaojiao; Zuo, Zhenghong; Wang, Chonggang
Highlights: Tributyltin exposure induced glucose intolerance and hyperinsulinemia in male mice. Tributyltin reduced both pancreatic β-cell mass and α-cell mass. Tributyltin down-regulated serum glucagon level and hepatic glucagon receptor expression. Tributyltin reinforced hepatic gluconeogenesis and increased hepatic glycogen content. Abstract: Some previous studies showed that organotin compounds induced diabetes in animal models. The underlying mechanisms should be further revealed. In this study, male KM mice were exposed to tributyltin (TBT) at 0.5, 5 and 50 μg/kg once every three days for 45 days. The TBT-treated mice exhibited an elevation of fasting blood glucose level and glucose intolerance. The fasting serum insulin levels were increased and reached a significant difference in the 50 μg/kg group; the glucagon levels were significantly decreased in all the treatments. Pancreatic β-cell mass was significantly decreased in all the treatments; α-cell mass showed a significant decrease in the 5 and 50 ug/kg groups. The transcription of pancreatic insulin gene ( Ins2 ) showed an up-regulation and reached a significant difference in the 5 and 50 μg/kg groups, which would be responsible for the increased serum insulin levels. The transcription of glucagon gene ( Gcg ) in the pancreas was significantly down-regulated in the 5 and 50 ug/kg groups. The protein expression of hepatic glucagon receptor was down-regulated, while the expression of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase was up-regulated accompanied by increased hepatic glycogen content. These results indicated that hepatic gluconeogenesis was enhanced during insulin resistance stage caused by TBT exposure, which would exert a potential risk inducing the development of diabetes mellitus.